A Study of the Concept of Juvenile Criminal Responsibility in Connection with a Specific Incident - Tüzün, Birgül; Elmas, İmdat and İnce, Cengiz Haluk and Akkay, Erdem (The Bulletin of Legal Medicine, 1997)
Two 14 years old male juveniles convicted of murdering a 13 year old female have been studied with the purpose of establishing their criminal responsibility. The factors which caused the crime, the nature of the execution, the convicts’ defense logic, their behaviour prior to, during and after the crime; and the revealed aspects of their physical, mental, emotional, moral and sociocultural development were examined respectively. Key Words: Juvenile, Crime, Criminal responsibility.